Speech fluency: a result of oral language proficiency - Balažic Bulc, Tatjana (Array, 2012)
Foreign language proficiency is also marked by speech fluency – defined as speech of normal frequency, without hesitation, interruption, repetition, correction, fillers and intermissions produced during the processing period that corresponds to the informative and communicative load of the utterance. Fluent speech involves inherent familiarity with various components of communication competence, from linguistic and textual to strategic, pragmatic and discursive ; therefore it requires a high level of proficiency in the first as well as in the second language. The paper presents an analysis of speech fluency on the example of Croatian as the second language. We aim to answer the question to what extent the speech fluency is influenced by the level of proficiency in a foreign language as compared to the effect of other cognitive abilities of a speaker. The analysis is based on measurements of time parameters and the occurrence frequency of individual forms of speech disfluency, comparison of relations between the individual parameters, and qualitative research on the sample of 14 speakers of Slovene as the first and Croatian as the second language (guided discussion on a familiar topic).